1973
DOI: 10.1002/polc.5070400124
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stabilization of dimethyl silicone fluids with iron between 70 and 370°C

Abstract: Long term oxidation tests below 150°C on dimethyl silicone (DMS) fluids with controlled iron content, in conjunction with previous work, have provided a broad concept of the processes of oxidation in DMS fluids between 70 and 370°C. A nonfree radical, iron‐catalyzed oxidation of DMS fluid occurs both below and above 150°C. A diverging, free radical chain reaction which is inhibited by iron is initiated by direct attack of oxygen on the methyl groups of DMS above 150°C. It is believed that a ferric iron complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Nielsen [18] has suggested that inhibitors of the oxidation of polydimethylsiloxanes may be divided into two groups. The first group includes compounds whose inhibiting capacity is used up in the process of oxidation -organic salts of iron and cerium, and the second group includes compounds whose inhibiting capacity remains constant -organosiloxy vanadates and certain metal oxides.…”
Section: Different Methods Exist For Introducing Stabilising Additivementioning
confidence: 99%
See 1 more Smart Citation
“…Nielsen [18] has suggested that inhibitors of the oxidation of polydimethylsiloxanes may be divided into two groups. The first group includes compounds whose inhibiting capacity is used up in the process of oxidation -organic salts of iron and cerium, and the second group includes compounds whose inhibiting capacity remains constant -organosiloxy vanadates and certain metal oxides.…”
Section: Different Methods Exist For Introducing Stabilising Additivementioning
confidence: 99%
“…Investigation of the mechanism of oxidation of the methyl group in polyorganosiloxanes in the presence of variable-valency transition-metal compounds [3,18] showed that by reacting with molecular products they initiate a chain radical process, and by reacting with free radicals they rupture the chains. Depending on the conditions, one of these functions of the catalyst may predominate, as a result of which it may act now as an initiating agent, now as an inhibitor.…”
Section: Heat-resistant Rubbersmentioning
confidence: 99%
“…These results are in agreement with the XRD analysis, and further conrm that Fe 3 O 4 is generated in the process of antioxidation. Moreover, the Fe 3+ (complex) is regarded as the composite of Fe 3+ on the surface of the a-Fe 2 O 3 complex with oxygen on the backbone of SR 13 (Fig. 5).…”
Section: Analysis Of 57 Fe Mössbauer Spectramentioning
confidence: 99%
“…9 Another simple and efficient method involves the use of antioxidation additives such as ferric oxide (Fe 2 O 3 ) and cerium oxide. [10][11][12][13] Fe 2 O 3 is a common and most effective heat-resistant additive, which signicantly improves the antioxidation of SR. Many studies have reported that Fe 2 O 3 could enhance the thermal stability of SR, [13][14][15][16] nevertheless, there is still no consensus about the mechanism of the antioxidation effect of Fe 2 O 3 on SR. Nielsen 13 suggested that free radicals are destroyed as a result of the reduction of the metal ion as follows:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation